Lactococcus Species Central Line-Associated Bloodstream Infection in Pediatrics: A Case Series - Firmani, Sarah E.; Maples, Holly D.; Balamohan, Archana (Frontiers in Medicine, 2022)
Lactococcus spp. is typically thought to be of low virulence and seldom considered pathogenic. Few cases of significant infections in children have been reported, all outside of the United States. There is also limited data on antimicrobial susceptibility testing for Lactococcus spp. We present 3 pediatric patients with central line bloodstream infections due to Lactococcus spp. between 2018-2020, along with a review of the pediatric literature.